Structure of the high efficiency the specialized calculator for modeling problems of navigation - Zhukov, I. A.; Sinelnikov, A. A.; Antipov, A. A. (Problems of Informatization and Control, 2007)
The problem of computer modelling of problems of navigation and traffic control of an air vessel is considered. The organisation of high-efficiency specialised structure for calculation of the sums of pair products of matrixes for the purpose of improving productivity of control systems and simplification the structural organisation of airboard computers is offered.